Conducta social percibida por los docentes e inteligencia emocional en alumnos del sexto grado Red N° 10 Callao - Martínez Hernández, Isolina Rosario (2012)
The research analyzes the association between perceived social behavior by 23 teachers and emotional intelligence of sixth graders Network 10 Callao in a sample of 240 students of 10, 11 and 12. We applied two instruments: the social behavior scale Meneses, adapted by Zamudio (2009) and the Inventory of emotional intelligence, Baron ICE: NA Ugarriza and adapted by Pajares (2005). Research applied descriptive correlational design. The results showed the existence of association between the two variables, students were observed inappropriate behavior, which would be associated with the low level of development of emotional intelligence. The dimensions friendship and group participation, shyness, negativity and selfishness and rivalry and litigation social behavior observed significant association regarding emotional intelligence.